On the relation between a green and bright window view and length of hospital stay in affective disorders. Issue 1 (22nd February 2022) - Mascherek, Anna; Weber, Sandra; Riebandt, Kevin; Cassanello, Carlos; Leicht, Gregor; Brick, Timothy; Gallinat, Jürgen; Kühn, Simone
Abstract: Background: The salutary effect of window views on greenery for inpatients in hospitals on length of stay and recovery rate has been repeatedly shown, however, not for psychiatric inpatients. The study assessed the association between a window view on green trees or man-made objects and brightness of the room on length of stay in a sample of psychiatric inpatients from one clinic. Methods: Data records of 244 psychiatric inpatients (mean age in years 41.8; SD = 11.8; 59.8% female, length of stay varying between 7 and 100 days) that were admitted between May 2013 and October 2018 with affective disorders were examined. Window view was assessed with images taken from each room and classified into showing man-made objects or green trees. The percentage of green within each image was also calculated as greenness of the view. Brightness was assessed with a luxmeter. Results: Although no effect was found for the dichotomous measures (man-made objects vs. green trees), a suppression effect emerged for percentage of green and brightness. The results indicate that both greenness of the window view as well as brightness significantly reduce length of stay in psychiatric inpatients with affective disorders. Conclusions: The suppression effect likely results from the characteristics of the windows; the greenest rooms also being the darkest. Due to the infrastructure of the ward, greenness and brightness came at the expense of each other. The results generally support the importance of a view into greenery and natural sunlight for recovery.